Frictional behaviour of imidazolium sulfate ionic liquid additives under mixed slide to roll conditions: part 2 — influence of concentration and chemical composition of ionic liquid additive. (26th February 2015) - Pejaković, V.; Igartua, A.; Kalin, M.
Abstract: Current work presents the investigation of frictional behaviour of ionic liquid lubricant mixtures under mixed slide to roll ratio. On the contrary to the previous study, which focuses on determination of the most suitable ionic liquid additive for identical ionic liquid weight concentration in lubricant mixture, this work had two scopes. The first one was to determine the optimal chemical composition of ionic liquid additive by investigating the lubricant mixtures with identical molar ratio, and the second one, to optimise additive concentration for certain ionic liquid structure. The changes were observed by two means. Namely, in frictional behaviour, ionic liquid concentration plays significant role. On the contrary, for the mixtures with identical molar concentration, the chemical structures with longer alkyl substituent do not always exhibit improvement. Experiments also revealed correlation between ionic liquid structures, concentration and wear. Atomic force microscopy (AFM) analysis of worn surfaces confirmed the above statements. Copyright © 2015 John Wiley & Sons, Ltd.